Orthogonal analysis of variants in APOE gene using in-silico approaches reveals novel disrupting variants - Li, Chang; Hou, Ian; Ma, Mingjia; Wang, Grace; Bai, Yongsheng; Liu, Xiaoming (Frontiers in Bioinformatics, 2023)
Alzheimer’s disease (AD) is one of the most prominent medical conditions in the world. Understanding the genetic component of the disease can greatly advance our knowledge regarding its progression, treatment and prognosis. Single amino-acid variants (SAVs) in the APOE gene have been widely investigated as a risk factor for AD Studies, including genome-wide association studies, meta-analysis based studies, and in-vivo animal studies, were carried out to investigate the functional importance and pathogenesis potential of APOE SAVs. However, given the high cost of such large-scale or experimental studies, there are only a handful of variants being reported that have definite explanations. The recent development of in-silico analytical approaches, especially large-scale deep learning models, has opened new opportunities for us to probe the structural and functional importance of APOE variants extensively. In this study, we are taking an ensemble approach that simultaneously uses large-scale protein sequence-based models, including Evolutionary Scale Model and AlphaFold, together with a few in-silico functional prediction web services to investigate the known and possibly disease-causing SAVs in APOE and evaluate their likelihood of being functional and structurally disruptive. As a result, using little to no prior field-specific knowledge, we reported 5 SAVs to be potentially disruptive, one of which (C112R) was classificed by previous studies as a key risk factor for AD. Our study provided a novel framework to analyze and prioritize the functional and structural importance of SAVs for future experimental and functional validation.